Co-inoculation Effect of Endophytic Bacteria with Mesorhizobium sp. in Chickpea (Cicer arietinum L.) on Nodulation, Yields, Nutrient Uptake and Soil Biological Properties - and Navneet Pareek, Monika Rana, Ramesh Chandra (Journal of the Indian Society of Soil Science, 2016)
Performance of 10 different endophytic bacteria on the root nodulation, growth and yields of chickpea and soil properties was evaluated in a field experiment during rabi season of 2013-2014 in a sandy loam soil at Pantnagar. Thirty-three endophytic bacterial strains were isolated from the roots and nodules of chickpea grown in different plots at Norman E. Borlaug Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar. Mesorhizobium sp. alone showed marginal benefits in nodulation, plant dry matter production, grain and straw yields, N and P uptake and soil biological properties. Combined use of Mesorhizobium sp. with different endophytic bacteria further increased the nodule number by 4.7 to 81.8 per cent, nodule dry weight by 2.3 to 69.3 per cent, and plant dry weight by 2.4 to 66.5 per cent, over Mesorhizobium sp. alone inoculation at different crop stages. Endophytic bacteria NE10 and NE14 also recorded significantly more grain yield of 18.4 and 17.1 per cent and straw yield of 26.1 and 27.7 per cent over Mesorhizobium sp. alone. The co-inoculated endophytic bacteria improved N uptake by grain from 16.1 to 44.3 per cent, N uptake by straw from 3.3 to 43.5 per cent, P uptake by grain from 10.5 to 39.7 per cent and P uptake by straw from 5.8 to 66.9 per cent over Mesorhizobium sp. alone. Combined inoculation of endophytic bacteria NE3, NE5, NE10, NE12, NE14, NE16, NE17 and R4 recorded significantly more microbial biomass carbon in soil over Mesorhizobium sp. alone at 45 days after sowing and harvest of crop. The co-inoculated endophytic bacteria also favoured the soil dehydrogenase and acid and alkaline phosphatase activities at both the intervals. The NE 10 was found most efficient in improving the nodulation, plant dry matter, yield, nutrient uptake and soil biological properties.